Upgrading of Philippine coals with emphasis on the application of the oil agglomeration technology - Herrera, Alice B.
Coal has the advantage of being an abundant energy resource in the Philippines. However, the uncontrolled utilization of coal, particularly low grade coal, using existing conventional technologies could have adverse effects on the environment on a local, regional and global scale. These adverse environmental effects of coal use, if not properly addressed, could hamper expanded coal utilization in the Philippines which is in line with the government's thrust on sustainable development. Aside from this, the Philippines is becoming more and more concern with its environment jut like the rest of the world. One of the promising techniques for handling very fine coal and recovering most of the carbonaceous material is called "oil agglomeration". Aside from being an efficient and effective technique to selectively separate coal from mineral matter and beneficiate the coal to a higher grade, oil agglomeration produces agglomerates which have a very good storage and handling properties and have low and consistent level of impurities.